Is There Volume Transmission Along Extracellular Fluid Pathways Corresponding to the Acupuncture Meridians? - Weibo Zhang; Ze Wang; Shuyong Jia; Yuying Tian; Guangjun Wang; Hongyan Li; Kjell Fuxe (Medical Association of Pharmacopuncture Institute, 2017)
Volume transmission is a new major communication signaling via extracellular fluid (interstitial fluid) pathways. It was proposed by the current authors that such pathways can explain the meridian phenomena and acupuncture effects. To investigate whether meridian-like structures exist in fish body and operate via volume transmission in extracellular fluid pathways, we injected alcian blue (AB) under anesthesia into Gephyrocharax melanocheir, which has a translucent body. The migration of AB could be seen directly and was recorded by a digital camera. The fish was then embedded and cut transversely to observe the position of tracks in three dimensions. Eight longitudinal threadlike blue tracks were recognized on the fish. The positions of these threadlike tracks were similar to meridians on the human body. Transverse sections showed that these tracks distributed to different layers of distinct subcutaneous loose connective tissues and intermuscular septa. Lymphatic vessels were sometimes associated with the extracellular blue tracks where the migration of AB occurred. Extracellular fluid pathways were found on fish through their transport of AB. These pathways operating via volume transmission appeared to be similar in positions and functions to the acupuncture meridians in Chinese medicine.